“COMPARING GOVERNMENT TRANSPARENCY AND ACCOUNTABILITY FOR ANTI-CORRUPTION PROGRAM: PERSPECTIVES FROM CHINA AND INDONESIA” - Bonaparte, Noni; Youran, Guo; Takeleb, Felicidade Victoria; Mapuasari, Supeni (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This article qualitatively overviews the corruption prevention policies of two countries, Indonesia and China. By conducting a literature and regulation analysis, also interview to some respondents, this article summarizes and describe the detail policy differences within two countries corruption eradication program. Reviewing country’s policy enables the public to better understand corruption form several points of views, such as punishments design, magnitude, potential losses, sanction threats, and sanction release. Besides understanding the history and phenomena of corruption, examining the potential impact of punishment regulations will enlighten the public understanding of corruption eradication policy.